Communism's postwar decade : the gains and losses of communist parties in the non-communist world since 1945 / by Simon Wolin ; introduction by Sidney Hook - Hook, Sidney (1902-1989); Wolin, Simon
En: The new leader. 32 aǫ de publicación, diciembre 1955